2021
DOI: 10.3390/rs14010171
|View full text |Cite
|
Sign up to set email alerts
|

Improved Active Deep Learning for Semi-Supervised Classification of Hyperspectral Image

Abstract: Hyperspectral image (HSI) data classification often faces the problem of the scarcity of labeled samples, which is considered to be one of the major challenges in the field of remote sensing. Although active deep networks have been successfully applied in semi-supervised classification tasks to address this problem, their performance inevitably meets the bottleneck due to the limitation of labeling cost. To address the aforementioned issue, this paper proposes a semi-supervised classification method for hypers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Wang et al [ 24 ] suggested a semi-supervised HSI classification model which improved deep learning. Here, the suggested model namely the arbitrary multiple graphs method, and then replaced skilled learning with the anchor graph method that could be labelled a significant unlabelled data automatically and precisely.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Wang et al [ 24 ] suggested a semi-supervised HSI classification model which improved deep learning. Here, the suggested model namely the arbitrary multiple graphs method, and then replaced skilled learning with the anchor graph method that could be labelled a significant unlabelled data automatically and precisely.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The main goal of such systems is to perform selected input queries against a large number of classifiers. When compared to random sampling, sample selection utilizing active learning (AL) [46] is more discriminative. The suggested work is based on the presence of a zone of uncertainty among a collection of training samples.…”
Section: Active Learningmentioning
confidence: 99%
“…Classification of hyperspectral images involves identifying various forms of information on Earth's surface using hyperspectral satellite data (Wang et al, 2021). This is achieved through the classification of satellite images, utilizing machine learning and deep learning techniques to identify areas containing various types of living organisms and objects (He et al, 2017).…”
Section: Introductionmentioning
confidence: 99%